Penentuan Faktor Kemiskinan Indonesia Menggunakan Regresi Logistik - Azis, Irfani; Sumertajaya, I Made; Purwaningsih, Siti Samsiyah; Tjahjawati, Sri Surjani (Jurusan Matematika FMIPA UNM, 2023)
Poverty is a global problem faced by various countries, including Indonesia. This study aims to determine the factors that influence the level of poverty in Indonesia by looking at the poverty classification itself. The data used is data on the website of the Central Statistics Agency and Bappenas in 2021 with the model used is an ordinal logistic regression model. The backward elimination method isused to select the best model with the lowest information criterion akaike value. The results of this study are that the gross domestic product factor and the unemployment rate have a significant positive effect, while population size and the provincial minimum wage have a significant negative effect on the poverty rate in Indonesia.